SEJARAH PERKEMBANGAN HUKUM - Anwar Anas; Muannif Ridwan; Raden Dimas Ari Wibowo; Dedy Suryadana; Asseri (Indra Institute Research & Publication, 2022)
Basically the law develops following the times in which every era the law changes according to human needs. With the development of science, the law is also growing because otherwise it will be left behind and all problems related to law will not be able to be handled properly. Human life needs law because law is a rule that regulates every individual. If in life there is no law that regulates it, humans will be arbitrary and all criminal and civil problems will not be resolved because there is no legal basis that regulates them. Law in Indonesia is very diverse ranging from customary law, criminal law, civil law to Islamic law. These laws have their respective roles and functions that cannot be separated from one another. Law has an important role in regulating the welfare and prosperity of the community because with the law all rules can be implemented and make the environment safer from criminal acts. Therefore, the birth of a law is a very useful thing for people's lives, especially Indonesia which is a state of law that is sovereign by the people based on Pancasila.